Effects of coarse woody debris on plant and lichen species composition in boreal forests. (27th December 2016) - Kumar, Praveen; Chen, Han Y.H.; Thomas, Sean C.; Shahi, Chander
Abstract: Question: Although the importance of coarse woody debris (CWD) for understorey species diversity has been recognized, the relative effects of coarse woody debris decay class and substrate species on understorey species composition have received little attention. We examined how the species composition of understorey vegetation change with CWD decay class and substrate species. Location: Boreal mixed‐wood forests, Ontario, Canada. Methods: To cover a wide range of CWD decay classes and substrate species, we sampled fire‐origin boreal forest stands that varied in stand age and canopy tree species composition. Vegetation on CWD was sampled by visually estimating percentage cover of each species within a 0.1 m × 0.5 m quadrat, randomly laid lengthwise on top of each sampled CWD log. We also recorded the forest floor vegetation by establishing an adjacent plot of the same size at a distance of 1.0 m in a random direction from the CWD vegetation sample. Results: Multivariate analysis showed that understorey species composition differed among decay classes and substrate species. A NMDS ordination of understorey species composition revealed a clear separation of decay classes 1 and 2 from higher decay classes, and that decay classes 4 and 5 shared several species with the forest floor. The species composition on the forest floor was completely different from the species composition on CWD decay classes 1, 2 and 3. Two distinct groupings of substrates according to CWD species composition were found: conifer species ( Pinus banksiana and Picea spp.) and broad‐leaf species ( Betula papyrifera and Populus spp.), with Abies balsamea taking an intermediate position. Indicator species analysis showed distinct understorey species affiliations to substrate species at advanced decay classes. Understorey species composition on the CWD of P. banksiana showed particularly pronounced changes from the dominance of lichens on decay classes 2 and 3 to dominance by mosses and vascular species on decay classes 4 and 5. Conclusions: Understorey species composition on CWD not only differed with decay class, but also with CWD substrate species. Conservation strategies should aim at retaining diversity of CWD in terms of both decay classes and species composition in boreal forests. Abstract : We examined the effects of coarse woody debris decay class and substrate species on understory vegetation communities and found that understory species composition on CWD not only differed with decay class, but also with CWD substrate species. Conservation strategies should aim at retaining diversity of CWD in terms of both decay classes and species composition in boreal forests.